Implementasi Merdeka Belajar Kampus Merdeka Terhadap Peningkatan Kapasitas Aparat Desa Dalam Hal Menyusun Peraturan Desa - Eko Nuriyatman; Muskibah Muskibah; Dessy Rakhmawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2024)
Community Service Activities to Build a Law Aware Village is an Independent Learning Independent Campus activity owned by the Law Study Program. The problem that partners have is the inability to compile village regulations and academic texts and determine the priority scale of what village regulations will be prepared by the village. So with the initial problem, the Community Service Team made a proposal by conducting counseling and mentoring through 6 (six) students involved in the Merdeka Belajar Kampus Merdeka Integrated Work Lecture. In addition to counseling carried out by competent teams and resource persons, students are given knowledge and skills to be able to assist the village in the preparation of academic manuscripts and draft village regulations. Through this mentoring activity, two draft village regulations related to Customary Villages and Tourism Villages were obtained.